A backward looking measure of the effective marginal tax burden on investment - Johannes Becker; Clemens Fuest (Center for Economic Studies and ifo Institute (CESifo), 2004)
Forward looking measures like the well-known effective marginal tax rate developed by King and Fullerton (1984) are often criticized for not taking into account the complexity of the tax law. This paper derives a method of evaluating this kind of measure and of quantifying the bias resulting from simplifying assumptions, especially on the pattern of depreciation deductions. We apply our method to German data and find that even small estimation biases in determining the tax deductions have a large impact on the effective tax rates for marginal and inframarginal investment projects. We conclude that our method may be used to quantify exactly the difference between the actual use of depreciation deductions and the King- Fullerton assumptions and therefore to correct the conventional forward looking measures.
Keywords: H25; H21; 330; effective tax rates; corporate taxation; Steuerbelastung; Grenzsteuersatz; Steuerwirkung; Unternehmensbesteuerung; Steuerbegünstigung; Theorie